A re-assessment of diversity among Philippine gymnures (Mammalia: Erinaceidae: Podogymnura), with a new species from eastern Mindanao - Balete, Danilo S.; Heaney, Lawrence R.; Rickart, Eric A.; Quidlat, Roselyn S.; Rowsey, Dakota M.; Olson, Link E. (Zootaxa, 2023)
Podogymnura, a Philippine endemic genus of gymnures (“soft-furred hedgehogs”), has been known previously only from the highlands of central Mindanao (P. truei truei and P. t. minima) and from two small islands off the northeast tip of Mindanao (P. aureospinula). Based on a combination of mitochondrial genetic and qualitative and quantitative morphological data, we recognize P. minima, formerly considered a subspecies of P. truei, as a distinct species. We also recognize specimens from two little-studied montane regions of southeastern Mindanao, Mt. Hamiguitan and Mt. Kampalili, as a distinctive new species, P. intermedia n. sp. We estimate that dispersal of a common ancestor from Borneo to Mindanao ca. 1.9 to 3.5 Ma gave rise to Podogymnura, followed by speciation within Mindanao beginning 0.53 to 0.97 Ma. These results further increase the rich diversity of mammals on Mindanao, and underscore the importance of the eastern Mindanao highlands as a likely important but little-studied center of Philippine mammalian diversity.